Silent disco: Dancing in synchrony leads to elevated pain thresholds and social closeness - Tarr, B; Launay, J; Dunbar, R (Elsevier, 2016)
Moving in synchrony leads to cooperative behavior and feelings of social closeness, and dance (involving synchronization to others and music) may cause social bonding, possibly as a consequence of released endorphins. This study uses an experimental paradigm to determine which aspects of synchrony in dance are associated with changes in pain threshold (a proxy for endorphin release) and social bonding between strangers. Those who danced in synchrony experienced elevated pain thresholds, whereas those in the partial and asynchrony conditions experienced no analgesic effects. Similarly, those in the synchrony condition reported being more socially bonded, although they did not perform more cooperatively in an economic game. This experiment suggests that dance encourages social bonding among co-actors by stimulating the production of endorphins, but may not make people more altruistic. We conclude that dance may have been an important human behavior evolved to encourage social closeness between strangers.